A essência do poder constituinte - Chiaradia, Tatiana Del Giudice Cappa (2009)
The Constituent Power is a mysterious and intriguing representation, it awakes the curiosity about the practicing of a power which is responsible for the elaboration of a Constitution, establishing the Constitutional State and creating the legal system of a nation. The practicing of the Constituent Power is the manifestation of the political power which belongs to the People, who relies on the State the power for regulating social relations, limiting its acting in order to assure fundamental rights, by using the ruling established in the Constitution. The objective of this study was analyzing the Constituent Power, in order to reveal its nature, its rationale, so that its identity can be defined allowing the analysis of a few interesting points about its reach. Considering that this study aimed at discovering the essence of the Constituent Power, concepts of Philosophy, Law, power, Constitution and Constitutional State were also investigated, enlarging the comprehension of what actually is the Constituent Power and the analysis of its manifestation, by using a zetetic (philosophical) focus, based on research of issues related to Law, Sociology, Politics, Economy and History. As consequence of the studies carried out, it became possible to realize that the power is characterized by the presence of an authority and of a hierarchic relation, due to which its withholder can grant his will to be fulfilled voluntarily by his addressees, being strongly related to matters of sovereignty and legitimacy. The Constitution is a set of juridical ruling responsible for the formation of the State, limiting the practice of the political power and assuring the fundamental rights of a person. It is the fundamental rule, featured of supremacy, which is positioned on the most elevated spot of the legal system, granting validity to any other juridical rules. The Constitutional State is an outgrowth of the elaboration of its Constitution by the Constituent Power, being conceived as a historical means for organizing political power, before a given society, in a given territory, in a given moment. As for the essence of the Constituent Power, it was identified as a political will which acts over a determined social structure, either in the practice of elaborating the Constitution of a country (Original), or in the elaboration of a Constitution of a State Member of a Federation (Resulting Derivative), or yet in the reformulation of the constitutional text (Resulting Reformer). The theory of the Constituent Power has been developed based on the manifest of Emmanuel Sieyès ( What is the Third Estate? ), which grants its title to the nation, with power to create the Constitution of a country